PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA EMPRESA PRODUCTORA Y COMERCIALIZADORA DE EMPANADAS DE PAPA CHINA (Colocasia Esculenta), PARA LOS AUTOSERVICIOS Y CAFETERÍAS EN LA CIUDAD DE LOJA - Paqui Zhunaula, Lus Angelina (2016)
The investigation work is reflected to the production of turnovers of Chinese potato with filler of cheese that will be marketed in the city of Loja, the same one that will have its respective facilities for the production in this sector, for the depreciation of the costs regarding the necessary resources, in what has to do with the matter it prevails required and the necessary manpower where you plantation the following topic: Creation of a company producer and comercializadora of turnovers of Chinese (Colocasia Esculenta) potato, for the self-service and cafeterias in the city of Loja; with the purpose of improving the economic situation of the sector and the productivity of the same one. For that which you plantation the following objectives: to develop a market study that allows to identify the opportunities and difficulties of the project inside a competitive market and this way to determine the offer and the demand; a technical study that allows to determine the size, localization and engineering of the project to settle down; to establish a study organization to establish the company type to be constituted and the design in agreement organization to the necessities of the company; to carry out a financial study to determine the I mount of the investments and the respective financing, costs and revenues that it generated the project, financial states and the balance point; to execute a financial evaluation through indicators as: VAN, TIR, RBC, PRC and ACE, making this way the feasibility of the project. For the market study it was applied 157 surveys to the owners of the cafeterias and supermarkets of the city of Loja and an interview carried out to a producing of semimanufactured turnovers, the same one that allowed to determine a wide unsatisfied demand of 511999 turnovers of Chinese potato. 5 In the technical study you could determine that the company will be located in the neighborhood Celi Román, parish Sucre of the city of Loja, the same one that has all the basic services. The company will have an installed capacity of 838656 turnovers of Chinese annual potato, I begin of the cycle of the production one worked with 39% of the installed capacity; the same one that will allow to produce 199680 annual turnovers. In the administrative study he/she settles down that the company will be conformed as Company of Limited Responsibility that will increase 5 work positions in the labor market when beginning its mercantile operations. For the installation of the project a total of the investment was determined of 22.904,57 dollars the same one that 56,34% will be financed by own capital and 43,66 remaining% by means of a financial institution with an interest rate of 12%, the production cost for the first year is of 118.328,06 dollars, with an entrance for sales of 139.627,11 dollars with an utility liquidate of 12709,14 dollars and a flow of effective of the one 10.111,90 dollars. When carrying out the financial evaluation you could determine what after having recovered the investment one will have a benefit of 38.870,92 dollars with an internal rate of return of 57,31% that is bigger to the discount rate; of each invested dollar one will have 26 cents of utility; the period of capital recovery is of 2 years, 2 months and 20 days; if the costs are increased until 3,61% or the revenues diminish 3,26% the project it is not sensitive; for what you can conclude that the project is feasible the indicators demonstrate financially since this way it.